Investigation of surface modification on aluminum oxide using acid etching surface pretreatment - Mohd Idham, Rosman (2012)
The current work focus on surface modification of aluminum oxide using acid etching surface pre-treatment. The main objective of this thesis is to investigate the effect of surface pre-treatment using acid etching on aluminum oxide (Al2O3) cutting tool. The effect of machining performance on alumina cutting tool using this pre-treatment in term of wear rate also studied. The scope of work include alumina as cutting tool, acid hydrofluoric for etching, PVD coating process and machining by turning operation. Alumina cutting tool was subjected to acid etching surface pre-treatment for 20 minutes before it was deposited with PVD coating process. Next, the cutting tool was test by turning machine in order to determine the wear resistant and other material characterization also was performed such as microstructure study, hardness Vickers test and surface roughness test. The current work result show shows a regular rough surface with no voids and crystals emerging from the as-received surface while a non-uniform surface topography with peak and valley after pre-treatment. The surface pre-treatment with HF acid provide rough surface to alumina microstructure. Besides, the machining test performance shows the coated alumina with acid etching surface pre-treatment provided longer tool’s life compared to as- received alumina and coated alumina without pre-treatment cutting tools. In addition, the micro hardness test indicated that average Vickers micro hardness of alumina as-received specimen was 1202.47 HV while coated alumina with acid etching pre-treatment specimen was 2293.43 HV. In surface roughness test, the surface roughness of alumina increase after subjected to pre-treatment but decrease after endergoes coating process. From the result, the acid etching surface pre-treatment and coating process affect the mechanical properties of alumina cutting tool such as microstructure, wear resistance, hardness and surface roughness.